Training for Intercultural Sensitivity Skills: A Case for Agricultural Extension Professionals in Nigeria and Nations Facing Similar Challenges - Bala M. Shehu (Journal of International Agricultural and Extension Education, 2018)
The agricultural sector is one of the biggest contributors to Nigeria’s economy in addition to being the employer of about 60% of its population (Odoemelam, 2011). In spite of the important role played by agriculture in the nation’s economy, the sector is still underdeveloped. To foster the development of agriculture in Nigeria, agricultural extension and advisory services are being used to transform the practices of farmers, who are still largely subsistence producers. In fact, Anaeto et al. (2012) attributed the slow development of Nigerian agriculture to the failure of its farmers to respond positively to novel ideas or innovations. For farmers to respond positively to such change, they must be properly educated on how best to implement the new ideas or practices on their farms. This is because increased agricultural productivity depends largely on the acceptance of cultural and technological transformations that extension workers bring to the farmers.
Keywords: agricultural extension; intercultural sensitivity; Nigeria; professional skills